Diverging Research Pathways in Islamic Capital Markets: A Bibliometric Study of Indonesia and Malaysia - Noval, Noval; Bachmid, Sofyan; Sofyan, Syaakir; MS, Syaifullah; Haekal, Ahmad; A. Rifai, Rachmawati; Nurdin, Muhammad Syarif (Journal of Islamic Economic and Business Research, 2026)
This study examines divergent research pathways in Islamic capital market (ICM) scholarship in Indonesia and Malaysia through a comparative bibliometric and thematic mapping approach. Based on 636 Scopus-indexed journal articles, comprising 212 Indonesia-affiliated records from 2012–2025 and 424 Malaysia-affiliated records from 2008–2025, the study applies Bibliometrix/Biblioshiny and VOSviewer to analyze publication growth, citation impact, influential actors, collaboration networks, keyword co-occurrence, thematic structures, co-citation networks, and knowledge evolution. The findings reveal two distinct but complementary trajectories. Indonesia shows faster recent growth and emerging visibility in sukuk, cash waqf, green sukuk, securities crowdfunding, financial inclusion, and sustainability-oriented Islamic finance, reflecting an acceleration phase shaped by development and inclusion concerns. Malaysia demonstrates a more mature and globally integrated research ecosystem, marked by higher productivity, stronger citation impact, productive institutional hubs, broader collaboration, and themes related to Islamic equities, portfolio diversification, bond yields, risk transmission, and market sophistication. The study contributes by showing that Indonesia–Malaysia differences reflect distinct knowledge-production models shaped by institutional maturity, regulatory ecosystems, and research infrastructure, thereby positioning Southeast Asia as a distinctive contributor to global ICM scholarship.